Midrange Reflection: The Underlying Practice of Wabash Center Workshops, Colloquies, and Consultations - Killen, Patricia O'Connell (Teaching theology and religion, 2007)
This article argues that the primary intellectual embodiment of the Wabash Center's ethos of hospitality is a particular kind of reflection on teaching and learning, “midrange reflection.” It defines and describes midrange reflection and then discusses the two essential skills required to facilitate it as distinct from other types of reflection and discussion: (1) the ability to identify issues in the life of a learning community, and (2) the ability to design sequences of questions and intellectual activities that promote reflection on those issues. As the underlying, if not defining practice of Wabash Center workshops, colloquies, and consultations, midrange reflection is crucial to the significant learning that occurs in Wabash Center programs and to participants’ ability to take their deeper understanding and insights back into their classrooms and professional lives.